Development of Pop Up Book Media Based on Qr Code to Improve Reading and Arithmetic Skills of Grade 2 Elementary School Students - Fitroh, Siti Khoirotul; Alfi, Cindya; Fatih, Mohamad (FKIP - Universitas Riau, 2024)
Based on the results of a survey conducted by researchers, many students in the class still have difficulty in working on story problems in mathematics learning. This encourages researchers to help improve students' reading and arithmetic skills. This study aims to determine the level of validity, feasibility and attractiveness of learning media in the form of QR code-based pop-up books to improve reading and arithmetic skills in addition and subtraction story problems for grade 2 students at UPT SDN Tlogo 02, Blitar Regency. The research method used is research and development (R&D) with the ADDIE model. The research stages include analysis of student needs and characteristics, design of pop-up book concepts and specifications, prototype development, implementation, and evaluation. The results of the study indicate that the QR code-based pop-up book developed is feasible and valid for use in terms of material, media, and language. This media is also an attractive media for students as seen from the results of the attractiveness questionnaire with a percentage of 90.94% and is included in the very attractive category. In addition, the media can help improve reading and arithmetic skills for grade 2 with an N-Gain calculation result of 0.5364. Based on these results, it can be seen that QR code-based pop-up book media is a feasible, valid and interesting media and can help improve students' reading and arithmetic skills.